2010
DOI: 10.1007/s00467-009-1294-7
|View full text |Cite
|
Sign up to set email alerts
|

Middle-term use of Cinacalcet in paediatric dialysis patients

Abstract: The effects of the calcimimetic drug Cinacalcet were assessed in six children with uncontrolled hyperparathyroidism secondary to stage 5 chronic kidney disease (CKD). Data were collected retrospectively regarding bone biochemistry and medications. Patients were between the ages of 11 months and 14 years on commencing Cinacalcet at initial doses of 0.4-1.4 mg/kg. Treatment, which was well tolerated in the majority and still on going in five patients, was for periods ranging between 3 months and 3 years. All six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Three recent articles demonstrated their efficacy in small groups of children with ESRD [9][10][11]. However, experience with cases of mutations in the receptor is very limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three recent articles demonstrated their efficacy in small groups of children with ESRD [9][10][11]. However, experience with cases of mutations in the receptor is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction in recent years of cinacalcet for the treatment of patients with primary hyperparathyroidism, as well as with secondary hyperparathyroidism due to endstage renal disease (ESRD), resulted in improved control of serum PTH and calcium in both adults and children [6][7][8][9][10][11]. At the time of writing, only one adult with symptomatic FHH has been reported to respond favorably to short-term treatment with cinacalcet [12].…”
Section: Introductionmentioning
confidence: 97%
“…Calcimimetics have been found useful in the few paediatric CKD-5 patients studied so far [110,111] . Six CKD 5D children aged between 11 mo and 14 years who had uncontrolled SHPT and treated with cinacalcet (doses: 0.4-1.4 mg/kg) showed satisfactory and sustained correction of the hyperparathyroidism [112] . Whatever medication that is chosen for the hyperparathyroidism, it is suggested that the target serum PTH in CKD 3, CKD 4, and CKD 5/5D should, respectively be in the 35-70, 70-110, and 200-300 pg/mL range to avoid adynamic bone disease from too low serum PTH [113] .…”
Section: Shptmentioning
confidence: 99%
“…In adult practice cinacalcet is used for the treatment of primary hyperparathyroidism and may delay the need for surgical intervention. Its use in children is evolving but it has been used in selected cases for primary hyperparathyroidism, neonatal hyperparathyroidism and in dialysis patients with secondary hyperparathyroidism 9 33 34…”
Section: Management Of Hypercalcaemiamentioning
confidence: 99%